2022
DOI: 10.1002/advs.202205247
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Nanovesicle‐Tandem‐Augmented Chemoimmunotherapy via Efficient Cancer‐Homing Delivery and Optimized Ordinal‐Interval Regime

Abstract: The strategy of combining immune checkpoint inhibitors (ICIs) with anthracycline is recommended by clinical guidelines for the standard-of-care treatment of triple-negative breast cancer (TNBC). Nevertheless, several fundamental clinical principles are yet to be elucidated to achieve a great therapeutic effect, including cancer-homing delivery efficiency and ordinal-interval regime. Tumor-derived extracellular vesicles (TDEVs), as vectors for intratumoral intercellular communication, can encapsulate therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In addition, previous studies have reported that PTX not only eliminated tumor cells directly but also induced the occurrence of ICD. Hence, whether Lip-CExo@PTX enhanced the PTX-induced ICD effect was then investigated. The ICD effect was characterized by increased exposure of dying tumor cells to damage-associated molecular patterns (DAMPs), including calreticulin (CRT) on the surface of the tumor and high mobility group protein box 1 (HMGB1) and adenosine triphosphate (ATP) in the extracellular tissue fluid. Thus, we examined the CRT expression of tumor cells coincubated with different drugs as well as the concentration levels of HMGB1 and ATP in the coincubated supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies have reported that PTX not only eliminated tumor cells directly but also induced the occurrence of ICD. Hence, whether Lip-CExo@PTX enhanced the PTX-induced ICD effect was then investigated. The ICD effect was characterized by increased exposure of dying tumor cells to damage-associated molecular patterns (DAMPs), including calreticulin (CRT) on the surface of the tumor and high mobility group protein box 1 (HMGB1) and adenosine triphosphate (ATP) in the extracellular tissue fluid. Thus, we examined the CRT expression of tumor cells coincubated with different drugs as well as the concentration levels of HMGB1 and ATP in the coincubated supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…Despite early challenges of low transfection efficiency, liposome formulations have been developed to deliver siRNA, plasmid DNA, and mRNA for gene silencing, replacement, and protein expression [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Surface modifications of liposomes with ligands, such as antibodies or peptides, have been a focus of research, enabling selective binding to specific receptors on target cells and improving delivery efficiency [ 12 , 13 , 35 , 36 , 37 , 38 ]. Additionally, stimuli-responsive liposomes were engineered to release their cargo in response to environmental cues, such as pH changes or ultrasound activity [ 37 , 39 , 40 , 41 ].…”
Section: Liposome-based Delivery Systemmentioning
confidence: 99%
“…Hybrid liposomes are liposomes that incorporate other elements, such as mesoporous silica [ 12 ] or exosomes [ 38 ], to enhance their delivery efficiency. The specific composition of hybrid liposomes varies depending on the intended application.…”
Section: Liposome-based Crispr Deliverymentioning
confidence: 99%
“…Anthracycline (ANT) is a first-line chemotherapy drug with high clinical efficacy and a broad antitumor spectrum ( 1 ). Adriamycin, daunorubicin, epirubicin, mitoxantrone and nordoxorubicin all belong to the ANT family of agents that are commonly used in clinical practice and widely used for treating hematological and solid tumors ( 2 ). As the clinical application of ANTs has become more common, clinical side effects on the heart following ANT treatment are also becoming gradually understood.…”
Section: Introductionmentioning
confidence: 99%